2015
DOI: 10.17305/bjbms.2015.616
|View full text |Cite
|
Sign up to set email alerts
|

Breast MRI, digital mammography and breast tomosynthesis: comparison of three methods for early detection of breast cancer

Abstract: Breast cancer is the most common malignancy in women and early detection is important for its successful treatment. The aim of this study was to investigate the sensitivity and specificity of three methods for early detection of breast cancer: breast magnetic resonance imaging (MRI), digital mammography, and breast tomosynthesis in comparison to histopathology, as well as to investigate the intraindividual variability between these modalities. We included 57 breast lesions, each detected by three diagnostic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 15 publications
3
44
2
2
Order By: Relevance
“…Some of the screening technologies that have been adopted include digital mammography, computer‐aided detection, breast MRI, and breast tomosynthesis. Each of these modalities holds the promise to improve screening performance for some women, but research is required at the population level and within the context of clinical practice to determine the conditions under which these modalities maximize benefit and minimize harm …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the screening technologies that have been adopted include digital mammography, computer‐aided detection, breast MRI, and breast tomosynthesis. Each of these modalities holds the promise to improve screening performance for some women, but research is required at the population level and within the context of clinical practice to determine the conditions under which these modalities maximize benefit and minimize harm …”
Section: Discussionmentioning
confidence: 99%
“…Each of these modalities holds the promise to improve screening performance for some women, but research is required at the population level and within the context of clinical practice to determine the conditions under which these modalities maximize benefit and minimize harm. 4 The primary benefit of screening with mammography is a decrease in breast cancer mortality. A study conducted by Myers et al in 2015 and meta-analysis done by Marmot et al concluded that mammography was estimated to reduce the risk of mortality by approximately 20%.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, many screening strategies have been widely used, such as mammography, breast magnetic resonance imaging (MRI) and ultrasound imaging. 7,8 However, these strategies are far from being perfect because of over-diagnosis, false-positive, inconsistent results and potential radiation injury. [9][10][11] Core needle aspiration can help establish the diagnosis, but the procedure is invasive and not suitable for routine use.…”
Section: Introductionmentioning
confidence: 99%
“…By combining information from different projections, DBT improves the differentiation of the adjacent anatomical structures, alleviating the superimposition effect [13]. More recent studies indicate about 30% increased DBT sensitivity and specificity compared with DM [14], with a 40% reduction in callback in screening [15-18]. DBT has been implemented in Kuwait during the last 5 years.…”
Section: Introductionmentioning
confidence: 99%